Pengaruh Pembiayaan Mudharabah terhadap Profitabilitas Return On Assets (ROA) pada PT Bank Syariah Indonesia Tbk (BSI) Periode 2015 – 2022 - Rica Octavia Trinanda; Wirman Wirman (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research was conducted aiming to determine the effect of mudharabah financing on the profitability of Islamic banks proxied by ROA (Return On Assets) with case studies on Indonesian Islamic banks for the 2015-2022 period. The method in this study uses a descriptive method with a quantitative approach. The data source used by the researcher is a secondary data source, namely the data obtained in this study are financial reports for quarters 1 to 4 at PT Bank Syariah Indonesia Tbk (BSI) for the period 2015 – 2022. The sampling method used purposive sampling. Data analysis techniques use classical assumption tests (Normality Test, Multicollinearity Test, Heteroscedasticity Test, and Autocorrelation Test). Furthermore, hypothesis testing (test statistic t, test statistic f, and test the coefficient of determination) with the help of SPSS version 16.0 for windows. Based on the tests that have been carried out, that mudharabah financing on the level of ROA obtained a result of 62.7%. These results indicate that mudharabah financing affects 62.7% of the profitability of Bank Syariah Indonesia, and the remaining 37.3% is influenced by other factors that are not present in this study. Thus the effect of mudharabah financing on profitability shows a result of 62.7% and is significant. So it can be concluded that mudharabah financing has a positive effect on the profitability of Bank Syariah Indonesia in the 2015-2022 period.